Creative Approach Guidance and Counseling Facing Independence Learning Policy: Minimum Competency Assessment and Survey Characters in the Industrial Revolution 4.0 - Rafki Nasuha Ismail; Mudjiran Mudjiran; Neviyarni Neviyarni; Herman Nirwana (Kurikulum Teknologi Pendidikan Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2020)
This article aims to explain how the creative approach of guidance and counseling in the face of independent learning in the era of Industry Revolusi 4.0 and preparedness counselor to minimum competency assessment and survey the characters. In principle already the task of counseling but counselors need creative approaches are required to utilize information technology as a means of supporting the counselor so that effective performance for different levels of education in the era of industrial revolution to four. The method used is descriptive qualitative study of literature. The results of several studies relevant journals obtained could be found the creative approach to guidance and counseling in facing the independent learning policy through the: first, assessment of minimal competencies which counselors provide career guidance services through ICT media. Such as